114 The prevalence of ECG abnormalities in young non-athletic individuals raises concerns regarding implementation of a nationwide screening program. (22nd September 2015) - Chandra, N; Rawlins, J; Papadakis, M; Edwards, C; Sharma, S
Abstract : Objectives: Pre-participation screening of competitive athletes, combining 12-lead ECG with a health questionnaire and physical examination, has been demonstrated to reduce the incidence of sudden cardiac death (SCD) over a long term follow up period. Paradoxically, the vast majority of SCD occur in the non-athletic population and in the absence of antecedent symptoms. In the UK, screening for sinister cardiac disorders is confined only to those individuals with symptoms, or in the context of a family history of premature cardiac disease. In this study we analysed the prevalence of ECG abnormalities in young non-athletic individuals. Methods: Between April 2006 and November 2009, 2619 subjects (mean age 18.3 years; range 14–35; 80% male) were investigated with a health questionnaire and 12-lead ECG. The questionnaire related to symptoms suggestive of cardiovascular disease and a family history of premature cardiovascular disease and/or SCD. The 12-lead ECGs were analysed for specific abnormalities as described in the European Society of Cardiology sports cardiology consensus. Specific criteria for an abnormal ECG analysed include P wave abnormalities suggesting left or right atrial enlargement; QRS abnormalities suggesting left ventricular hypertrophy, interventricular conduction delay and frontal plane axis deviation; and ST segment depression and T wave flattening or inversion. Results: Of the 2619 individuals investigated a total of 505 (19.3%) individuals demonstrated one or more abnormalities on the 12-lead ECG. The abnormal findings are summarised in the table below: Conclusions: These results demonstrate that there is a high prevalence of ECG abnormalities when applying the ESC sports cardiology consensus criteria to young non-athletic individuals. Many of these abnormalities are non-specific in isolation and warrant further investigations to be carried out. This has significant implications on the feasibility and cost-effectiveness of a national cardiovascular screening programme for sinister cardiac disease.